Enhancing Effective Learning among Children in Nursery and Primary Schools: Exploring Methodological Approaches - Iliasu, Femi Samuel; Hakeem, Nafiu Ayodeji; Sulaimon, Jamiu Temitope (Journal Of Teaching And Learning In Elementary Education, 2024)
Education is crucial for national development, positively impacting socio-cultural, political, economic, and human aspects of nation-building. This research explores strategies to enhance effective learning among children in nursery and primary schools within Ilorin South Local Government, Kwara State, Nigeria. The study employed a descriptive survey method, involving 100 respondents from 10 selected schools. Data were collected using a structured questionnaire, validated by experts with a reliability index of 0.72. The findings revealed that effective teaching methods included the play way method, educative rhymes, teacher demonstrations, and storytelling, while music was less effective. Major obstacles identified were the high cost of modern equipment, inadequate teacher training, young age of pupils, inadequate school facilities, lack of experience in handling children, poor teacher remuneration, and lack of interest from teachers. However, the lack of in-service teacher training was not a significant obstacle. It is recommended that schools be equipped with adequate facilities and employ qualified teachers. Additionally, diverse teaching methods should be used to effectively enhance learning in nursery and primary schools. Involving parents in contributing resources to school care centers is also suggested to support the development of these educational institutions.